CARDIOPROTECTIVE AND NEPHROPROTECTIVE EFFECTS OF ANGIOTENSIN CONVERTING ENZYME INHIBITOR RAMIPRIL - D. A. Napalkov; E. N. Golovenko (Столичная издательская компания, 2016)
There is grate interest to ACE inhibitors which have cardioprotective and neproprotective effects. Ramipril efficacy in ischemic heart disease prevention as well as ramipril positive effect on myocardium in adolescents is presented on the base of some trails. Ramipril ability to delay of diabetic and non-diabetic nephropathy progression is also discussed.